2020
DOI: 10.1111/aji.13370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a gestational level of estradiol on cellular transition, migration, and inflammation in cervical epithelial and stromal cells

Abstract: Problem Estrogen (E2) is one of the main steroid hormones associated with pregnancy and parturition. High levels of E2 increase uterine contractions, promote fetal membrane weakening, and induce degradation of the cervical extracellular matrix (ECM). Current evidence supports the role of E2 in epithelial‐to‐mesenchymal transition (EMT) and inflammation in different cell types; however, its effects on the cellular components of the cervix are still unknown. Method of study In this study, we assessed the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
3
18
0
Order By: Relevance
“…The immortalized ectocervical and endocervical epithelial cells used in this study were previously characterized and were shown to have conserved toll‐like receptor (TLR) expression when compared to primary ectocervical and endocervical epithelial cells 25,26 . The cells were immortalized by transduction with PA317⁄LXSN‐16E6E7‐conditioned medium (HPV16 E6/E7 immortalization) and cultured in keratinocyte serum‐free medium (KSFM) (37010022; Thermo Fisher Scientific), a culture medium that is highly selective for epithelial cells, supplemented with bovine pituitary extract (30 μg/mL), epidermal growth factor (0.1 ng/mL), CaCl 2 (0.4 mM), and primocin (0.5 mg/mL) (ant‐pm‐1; Invivogen; San Diego, CA) at 37°C in a 5% CO 2 environment, and grown to 80% confluence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The immortalized ectocervical and endocervical epithelial cells used in this study were previously characterized and were shown to have conserved toll‐like receptor (TLR) expression when compared to primary ectocervical and endocervical epithelial cells 25,26 . The cells were immortalized by transduction with PA317⁄LXSN‐16E6E7‐conditioned medium (HPV16 E6/E7 immortalization) and cultured in keratinocyte serum‐free medium (KSFM) (37010022; Thermo Fisher Scientific), a culture medium that is highly selective for epithelial cells, supplemented with bovine pituitary extract (30 μg/mL), epidermal growth factor (0.1 ng/mL), CaCl 2 (0.4 mM), and primocin (0.5 mg/mL) (ant‐pm‐1; Invivogen; San Diego, CA) at 37°C in a 5% CO 2 environment, and grown to 80% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemical staining for vimentin (3.7 µL/mL; ab92547; Abcam, Cambridge, MA, USA) and cytokeratin‐18 (CK‐18; 1 µL/mL; ab668; Abcam) was performed after 96 hours, as previously described 26,29 . Manufacturer’s instructions were used to calculate the staining dilutions to ensure uniform staining.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also shown that infection and inflammation can promote EMT in cervical epithelial cells ( 81 , 86 , 87 ). EMT was shown to be involved in the cervical changes that happen during parturition.…”
Section: Infection Inflammation and Cervical Remodelingmentioning
confidence: 68%
“…Cervix is composed of the epithelial and the stromal layer. The epithelial layer lining the cervical canal is divided into three distinct regions: the ectocervix, the transformation zone, and the endocervix, while the stromal layer is composed mainly of the extracellular matrix (ECM) incorporating fibroblasts, immune, and smooth muscle cells ( 44 , 88 - 91 ). As mentioned above, cervical remodeling is a required process to maintain pregnancy and like fetal membranes, multitudes of cellular matrix remodeling are needed to maintain cervical integrity, maintenance of intact tissue, and natural production of antimicrobial peptides to reduce the influx of vaginal microbiome and provide the barrier functions.…”
Section: Cervical Tissue and Oxidative Stressmentioning
confidence: 99%